Casa abrigo para mulheres vítimas de violência - Aschidamini, Milena Lasari (2022)
This paper discusses the struggle of women for gender equality and the prevalence of the macho culture in society. Considering the current context, and the situation of social isolation resulting from the Covid 19 Pandemic, it brings data as worrying indicators regarding domestic violence against women. Therefore , the present work of course conclusion has as purpose the development of a shelter house for women victims of violence, in the city of Passo Fundo - RS, aiming to propose an adequate space to receive the victim in situation of vulnerability, aiming the progress and the feminine empowerment, removing them from the situation of risk in which they live and making the architecture be the main transforming agent in the treatment of the women. The house has a temporary shelter, aiming to offer support in different emotional, personal, and physical aspects necessary for their restructuring.